(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This study aims to investigate the relationship between Intrinsic Leisure Time Motivation and Serious Leisure Time of handball athletes according to different variables. Accordingly, 88 individuals, 34 males, and 54 females, who played in professional handball leagues in Elazig, Turkey in 2022, participated in the study. The Serious Leisure Inventory and Measurement (SLIM) scale (12 items and 3 factors), which was developed by Ozdemir et al. (2020), and the Intrinsic Leisure Motivation Scale (ILMS) (23 items and 5 factors), which was developed by Ozdemir et al. (2020), were used in the study. The statistical analyses of the study were conducted in SPSS 24 package software. In the study, the independent samples t-test was used to compare the variables with two groups while the one-way variance analysis (ANOVA) to compare the variables with more than two groups. Furthermore, the Tukey test was conducted to determine the source of the differences obtained from the results of the one-way variance analysis (ANOVA). Finally, the Pearson correlation test was conducted to investigate the relationship between the scales and the factors of the scales. According to the results of the study, there was no relationship between the age groups and active handball-playing period, and the intrinsic leisure motivation levels and serious leisure time levels of the handball athletes. In the subscales of the intrinsic leisure motivation scale, it was observed that the handball athletes playing for 1-2 years had higher levels of struggle/proficiency compared to the athletes who played for 3-4 years and athletes who played for 7 years or longer based on the active handball-playing period variable. In the subscales of the serious leisure time, it was observed that the athletes who exercised for 1-2 days a week had higher levels of perseverance/effort and permanent acquisition compared to the athletes who exercised for 5 days and longer based on the weekly exercise frequency variable. Additionally, it was observed that handball athletes who stated that their income statuses were high had higher levels of identification with occupation, social gain levels, and permanent acquisition levels compared to the handball athletes who stated that their income statuses were low. Finally, it was determined that as the serious leisure time levels of the handball athletes increased, their intrinsic leisure time levels also increased.